Two new species of the mealybug genus Paraputo Laing (Hemiptera, Pseudococcidae) from Borneo Island, Indonesia - Agustin Zarkani; Habib Al Ayubi Reonaldi; Ariffatchur Fauzi; Dwinardi Apriyanto; Yahumri; Rosfiansyah; Mehmet Bora Kaydan (ZooKeys)
The mealybug genus Paraputo Laing (Hemiptera: Coccomorpha: Pseudococcidae) contains 89 species worldwide, including several important agricultural insect pests. During a 2024 survey of mealybug species on Borneo Island, Indonesia, two undescribed Paraputo species were found feeding on forest trees. Descriptions of both new species, based on morphological characters, are accompanied by photomicrographs and taxonomic illustrations. The newly described species, Paraputo raufi Zarkani & Kaydan, sp. nov. and Paraputo martonoi Zarkani & Kaydan, sp. nov., are each compared with other species of Paraputo to which they show notable morphological similarities. An updated taxonomic key to species of Paraputo found in Southeast and southern Asia is provided.